The in vitro and in vivo anti-inflammatory and anti-oxidative effects of an amino acid blend supplemented feed on pigs experimentally challenged with Salmonella Typhimurium - Ham, Sehyeong; Suh, Jeongmin; Kim, Jieun; Gu, Min Jeong; Park, Min Ah; Oh, Eunseon; Moon, Jun-Ok; Chae, Chanhee (Frontiers in Veterinary Science, 2024)
Background: The in vitro and in vivo anti-inflammatory and anti-oxidative effects of an amino acid (AA) blend (tryptophan, threonine, and methionine) for pigs. Objective: To evaluate the in vitro anti-inflammatory and anti-oxidative effect of an AA blend on intestinal porcine epithelial cells (IPEC-J2) and the in vivo anti-inflammatory and anti-oxidative effects to pigs experimentally challenged with Salmonella Typhimurium. Methods: IPEC-J2 were pretreated with AA blend for 25 hours and then, treated with lipopolysaccharide (LPS) and deoxynivalenol (DON), or H2O2 for in vitro evaluation. A controlled standard diet supplemented with 0.3% of the AA blend was orally fed to treated group pigs for 14 days beginning at 21 days of age. At the end of the feeding period, pigs were orally inoculated with Salmonella Typhimurium. Results: Pre-treatment with AA blend reduced LPS/DON-induced interleukin (IL)-8 mRNA as measurement of anti-inflammatory effect and H2O2-induced reactive oxygen species as measurement of anti-oxidative effect on IPEC-J2. Feeding with an AA-blend resulted in a reduction of pro-inflammatory (tumor necrosis factor-, IL-6, and IL-8) cytokine levels, while treated pigs experienced an increase in anti-inflammatory IL-10 cytokine in their sera. The addition of an AA blend supplemented pig feed resulted in significantly lower Salmonella-induced cecal lesion scores compared to untreated pigs. Discussion: Supplementation of feed with an AA blend reduced intestinal inflammation and pathology in pigs and may be applied for the control of Salmonella Typhimurium infection as demonstrated in this study.